TEACHING MEDICAL ENGLISH FOR FOREIGN STUDENTS USING INTERNET TECHNOLOGIES - To‘htasinova Fotimaxon Ravshanbek qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: The rapid development of digital tools and online learning platforms has significantly transformed the field of medical education. One of the most promising directions is the teaching of Medical English to foreign students through internet technologies. This paper explores the effectiveness of digital methods in enhancing medical language competence, improving communication skills, and providing access to authentic medical contexts. It highlights the role of interactive technologies, online resources, and virtual simulations in creating an engaging and student-centered learning environment.